2022
DOI: 10.1021/acs.jpcc.2c06114
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Random Lasing in MAPbI3 Halide Perovskite Single Crystals

Abstract: Halide perovskites are a promising optical gain media for lasers. In this work, the phenomenon of random lasing is studied in the halide perovskite MAPbI3 single crystal at a temperature of 4 K and pico- or femtosecond pulsed optical pumping. Spectral, temporal, polarimetric, and threshold measurements facilitate isolating random lasing from the photoluminescence background. Spectral localization of the lasing lines points to defect-related states emission as the lasing origin. Time-resolved photoluminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Interestingly, understanding the nature of defect‐related states is also relevant to application in lasing since these states are implied in the mechanism of lasing in HPs. [ 83 ]…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, understanding the nature of defect‐related states is also relevant to application in lasing since these states are implied in the mechanism of lasing in HPs. [ 83 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they are known for light amplification. 84,85 The observed fluorescence color of perovskites is subject to several factors, such as chemical composition, crystal structure, and nanoparticle size. A noteworthy attribute of perovskites is their capacity to exhibit different light colors, which is commonly known as multicolor tunability.…”
Section: Up-conversion Of Energy For Rgb and Wlmentioning
confidence: 99%
“…These states are generally undesirable in most cases; however, it has been reported that they are essential for lasing in halide perovskites. 12,13 In the PL spectra of MAPbCl 3 , the presence of many narrow lines in the region of defect-related states was reported. However, there are conflicting interpretations of these spectral lines in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite its high applicability potential and the highest stability among other MA-based perovskites, there is a significant knowledge gap in the fundamental properties of this material, particularly regarding defect-related states. These states are generally undesirable in most cases; however, it has been reported that they are essential for lasing in halide perovskites. , …”
Section: Introductionmentioning
confidence: 99%